Acceptance in implementation of Malaysian Sustainable Palm Oil (MSPO) among oil palm smallholders / Nor Amirah Ahmad - Ahmad, Nor Amirah (Faculty of Plantation and Agrotechnology, 2018)
The oil palm industry in Malaysia plays an important role in the growth of the agricultural sector in this country through its contribution to the Gross Domestic product (GDP), foreign exchange, and employment. Oil palm demands are continual increasing as it can produce high yield and low production cost. The present study aimed to investigate the acceptance in implementation of Malaysia Sustainable Palm Oil (MSPO) among oil palm smallholders in Gersik, Tangkak, Johor. The result observed several socio-economic factors that can lead to the implementation practices such as cost implementation of MSPO, smallholder's income, smallholder's knowledge and government policy regarding of MSPO. The study was conducted using questionnaires that were distributed to 52 samples of respondents. The data retrieved from conducted experiment was analyzed by using the Statistical Package for Social Sciences (SPSS) on Reliability test, Regression and Pearson Correlation analysis. The result shows that all the factors which are cost, income, knowledge and government policy have significant relationship towards the acceptance of smallholders in implementation of MSPO. Besides, knowledge is the most factor influence on implementation of MSPO. The key aspects for recommend are the necessary for an awareness campaign through such approaches as meetings, announcements, publications, and media. So that, the constraint of smallholders that never heard and have no idea about (MSPO) can be addressed.